Metodologia U-Pb em zircão por LA-Q-ICP-MS no laboratório Pará-Iso/UFPA - MIRANDA, Caio Cruz de (2025)
This work was developed in order to the implementation and detailed description of the experimental protocol of the U-Pb methodology in zircon by mass spectrometry in equipment with inductively coupled plasma source, model iCAP-Q from Thermo Fisher brand, with laser probe Nd: YAG LSX-213 G2 CETAC and Quadrupole type mass analyzer (LA-Q-ICP-MS), belonging to the Isotopic Geology Laboratory of the Federal University of Pará (Pará-Iso). The U-Pb geochronological system has been used by the geoscientific community for over 30 years and is currently a tool with high performance in specific analyzes of different minerals. Over the years, several studies have been carried out to improve the results obtained by the uraniumlead method, however, the analytical protocols of the LA-Q-ICP-MS technique are still little known in the literature. The experimental procedure used in this study was adapted from that already routinely used in Pará-Iso for zircon analysis by multi-collector LA-ICP-MS. The reference materials (RMs) adopted for the validation of the methodology consist of zircons already established as international RMs (BB, 91500 and Mud Tank), and were analyzed repeatedly in different analytical sessions to test the reliability, precision and reproducibility of the method and analytical data. The verification of examples of geological application was based on the various analyzes carried out by different researchers at Graduation, master’s and Doctorate levels, within the scope of Pará-Iso, in different types of rock and various geological environments (Amazonian Craton, Borborema Province, Paraguay Belt, Central Iberian ZonePortugal and São Luís Craton), highlighting the Carajás Province (Southeast of the Amazonian Craton) as the most studied terrain (n=2107). LA-Q-ICP-MS analyzes performed during the years 2021 and 2022 on zircon BB provided a mean 206Pb/238U age of 560 ± 1 Ma (MSWD= 1.12; n=373); for zircon 91500 the calculated age was 1069 ± 4 Ma (MSWD=1.5; n= 43) and 730 ± 17 Ma (MSWD=1.3; n= 30) for zircon Mud Tank. These results corroborate data published by other authors and laboratories, showing excellent accuracy, reproducibility, and average precision from 0,09% to 0.18% of the U-Pb methodology in zircon by LA-Q-ICP-MS at the Pará-Iso Laboratory, already in routine and available to the geoscientific community.